Classification of Malignant Melanoma and Benign Skin Lesion with the Aid of Using Back Propagation Neural Network and ABCD Rule - Sharma, Varun; Garg, Ananth; S. , Thenmalar (International Journal of Psychosocial Rehabilitation, 2020)
Melanoma skin malignant growth recognition at a beginning time is significant for a productive treatment. As of late, it is broadly perceived that the most extreme risky state of skin malignant growth in a portion of different types of pores and skin disease is melanoma because of the reality that it’s substantially more liable to unfurl to different parts of the body if not perceived and taken care of right on time. The non-obtrusive clinical PC, creative and judicious, or clinical picture preparation assumes a progressively immense job in the clinical conclusion of various illnesses. Such systems offer a programmed photo investigation gadget for a right and quick assessment of the injury. The means stressed right now are gathering dermoscopy picture databases, preprocessing, division, measurable component extraction, the utilization of Gray Level Co-event Matrix (GLCM), asymmetry, border, color, diameter (ABCD), and so forth. And afterward classification, the utilization of a back propagation neural network (BPN). The outcomes show that the executed order exactness is 75%.